Ketamine Revisited New Insights into NMDA Inhibitors - Saiz-Sapena, Nieves; Granell-Gil, Manuel (IntechOpen, 2022)
In the past, ketamine was considered a dangerous medication with the potential for abuse as a recreational drug. Healthcare providers were warned of its dangers and taught to fear its use. With this book, we hope to eliminate any fear and misgivings associated with this drug. It can be a useful medication in many situations, some of which we describe herein. This book discusses the use of ketamine in anesthesia, pain disorders, depression, palliative care, and trauma situations. It also examines ketamine usage in developing countries.